Research Paper: Effectiveness of Social Skills Training on Behavioral Problems in Adolescents with Intellectual Disability - Abbas Nesayan; Roghaie Asadi Gandomani (University of Social Welfare and Rehabilitation Sciences, 2016)
Objective children and adolescents are faced with wide range of social challengeable situations every day. Intellectual Disability is a condition that determined by significant limitations both in intellectual functioning and in adaptive behavior. This condition occurs before the age of 18 years. The prevalence of intellectual disability is estimated to be at 1-3% of the total population.  Children and adolescents with intellectual disabilities have deficits in social skills and hence, require social skills training.  It is important for students with intellectual disability to make and maintain positive social relationships with family, peers, teachers and other community members. Social skill training will have the most positive effects on the behavior of students with intellectual disability during the adolescence period. The present study was designed to investigate the effect of social skills on behavioral problems in adolescents with intellectual disability. Materials & Methods This was a quasi-experimental research with pretest and posttest and a control group. The study population included 28 adolescents aged 14-16 years with mild intellectual disability in Tehran who were selected using the convenience sampling method.  The subjects were randomly assigned into control and experimental groups. The experimental group participated in a training program for 10 sessions. In these sessions, social skills were taught individually. The control group did not receive any social skills training. After this stage, problem behaviors questionnaires were completed by all subjects (control and experimental group). The data obtained was analyzed using descriptive statistics (such as mean, standard deviation and Kolmogorov-Smirnov test for normality of the data) and inferential statistics (such as analysis of covariance). Results It was found that despite the difference in pre-posttest mean between both the groups, social skills training did not have any significant effect on the behavioral problems of students with intellectual disability (P>0.05). Conclusion This research showed that social skills training were not significantly effective on behavioral problems in adolescents with intellectual disability. Although our results were not effective, research evidence shows that people with cognitive delays (such as intellectual disability) require social skill training programs that include all of their academic, career, daily life, and social skills. As social skills learning plays a role in personal and social adjustment, it is necessary to pay more attention to these skills.